Development of Polymeric Materials as Hydrogels with Curcumin for Skin Tissue Regeneration - Pérez Ruiz, Mateo; Flores Merino, Miriam Veronica; Gonzalez Ruiz, Abraham (Revista Mexicana de Ingenieria Biomedica, 2024)
The aim of this review is to highlight advances in the development of hydrogels and the use of curcumin in the treatment of chronic wounds. Chronic wounds, such as pressure, vascular, neuropathic and neoplastic ulcers, represent a significant global health problem, accounting for 1-2 % of all existing wounds, and in Mexico alone, 9.4 % of the adult population suffers from chronic wounds, exacerbated by complications of diabetes mellitus. This systematic review used the virtual library OMICsearch and the search engine Mendeley, considering research that included some of the keywords such as biopolymers, curcumin, chronic wounds and hydrogels, so any that were not related to these and that did not fall within the search period between 2006 and 2024 were discarded. We found from 51 selected articles that curcumin, a phytopharmaceutical with antioxidant, anti-inflammatory and proangiogenic properties, has been shown to be effective in wound healing. Moreover, hydrogels offer significant advantages in wound treatment due to their ability to provide spatiotemporal control in the healing stages, regulate wound microenvironments and release active molecules in a controlled manner. In conclusion, although the skin is the largest organ of the body and commonly affected by wounds, wounds can also occur in other areas due to surgery, cancerous tumors and ulcers of various etiologies. The development of curcumin hydrogels not only focuses on skin wounds, but also addresses inflammatory diseases, tumors, liver diseases, asthma and osteoarthritis, with pharmaceutical and cosmetic applications.